8=-8u+4(u+3)

Simple and best practice solution for 8=-8u+4(u+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8=-8u+4(u+3) equation:



8=-8u+4(u+3)
We move all terms to the left:
8-(-8u+4(u+3))=0
We calculate terms in parentheses: -(-8u+4(u+3)), so:
-8u+4(u+3)
We multiply parentheses
-8u+4u+12
We add all the numbers together, and all the variables
-4u+12
Back to the equation:
-(-4u+12)
We get rid of parentheses
4u-12+8=0
We add all the numbers together, and all the variables
4u-4=0
We move all terms containing u to the left, all other terms to the right
4u=4
u=4/4
u=1

See similar equations:

| -2(4x-13)-7=10 | | 20.67x=62.01 | | -5x+4=4x | | 25=v+10 | | 144+5x+6=180 | | 6x+12=18x+9 | | 5=1/4g+3 | | 7c+10=10+7c | | 14+2x=-5x-2+5x | | 115+x=21 | | (3x-12)=78 | | 106=10-6x | | 36+12x=16+8x | | 6x-38+6x-38=5x+8 | | 4/3​b−14=15 | | 27-2x=20+5x | | –8–3k2=11 | | n4/2-3=13 | | 4(x+9)=15x-19 | | 6x10=-8 | | 63=7x+98 | | 3x+6=9x+30=90 | | 2x²+6x-1=x²+6x | | 2(6x-9)-6=-3-4(-3x+5) | | 2=t+5/3 | | 4b=-4b=8b | | 43​ b−14=15 | | -4k=76 | | 4x+11=3x+1=180 | | 37=7-6z | | 5x+35+10x+10=180 | | 7(x-1)=5x+19 |

Equations solver categories